Identification of endoscopic predictors of biliary malignancy during digital cholangioscopy. Issue 6 (22nd March 2022) - El Bacha, Hicham; Harizi, Rafik; Laugier, René; Lorenzo, Diane; Rivallin, Paul; Leblanc, Sarah; Barange, Karl; Fumex, Fabien; Laquière, Arthur; Napoléon, Bertrand; Vedrenne, Bruno; Grabar, Sophie; et al.
Abstract : Objectives: Biliary brushings and biopsies obtained during endoscopic retrograde cholangiopancreatography (ERCP) have a low sensitivity for the diagnosis of malignant biliary strictures. While cholangioscopic analysis is useful, visual criteria have not yet been defined. The aim of this study was to identify visual criteria for the diagnosis of indeterminate biliary strictures (IDBS). Methods: A multicenter study was conducted based on the analysis of cholangioscopic recordings of IBDS. Diagnostic criteria were identified in a study group and verified in a validation group. Results: Four criteria were identified to be associated with malignancy, one negatively ("endobiliary material, " odds ratio [OR] 0.62, 95% confidence interval [CI] 0.41–0.92) and three positively ("vascularized villous projections, " OR 1.52, 95% CI 1.03–2.24; "twisted or dilated vessels, " OR 2.18, 95% CI 1.47–3.24; and "dark color of the mucosa, " OR 1.82, 95% CI 1.23–2.70). Between two playbacks, the mean (95% CI) sensitivity of the observer's visual diagnosis increased from 66.1% (60–72) to 73.8% (69–78) ( P = 0.004); in the second playback, the kappa value for interobserver agreement ranged between 0.36 (color) and 0.56 (endobiliary material), with a significant improvement ( P = 0.0031–0.0001) between the first and second playbacks. Blind assessment by endoscopists not involved in this study had a diagnostic accuracy of 73% (71.4–74.5). Conclusion: The four identified cholangioscopic features are easy to implement in clinical practice and have the potential to increase the level of diagnostic confidence during the workup of IDBS.